Association of Vasculitis and Familial Mediterranean Fever - Abbara, Salam; Grateau, Gilles; Ducharme-Bénard, Stéphanie; Saadoun, David; Georgin-Lavialle, Sophie (Frontiers in Immunology, 2019)
Certain types of vasculitis occur more frequently and present differently in patients with familial Mediterranean fever (FMF). We assessed the characteristics of patients with FMF and systemic vasculitis through a systematic review of the literature. Medline was searched by two independent investigators until December 2017. We screened 310 articles and selected 58 of them (IgA vasculitis n=12, polyarteritis nodosa (PAN) n=25, Behçet’s disease (BD) n=7, other vasculitis n=14). Clinical case reports were available for 167 patients (IgA vasculitis n=46, PAN n=61, BD n=46, other vasculitis n=14), and unavailable for 45 patients (IgA vasculitis n=38, PAN n=7). IgA vasculitis was the most common vasculitis in FMF patients with a prevalence of 2.7-7%, followed by PAN with a prevalence of 0.9-1.4%. Characteristics of FMF did not differ between patients with and without vasculitis. Patients with FMF and IgA vasculitis displayed more intussusception (8.7%) and possibly less IgA deposits on histological analysis than patients with IgA vasculitis alone. Patients with FMF and PAN had a younger age at vasculitis onset (mean age = 17.9 years), as well as more perirenal hematomas (49%) and CNS involvement (31%) than patients with PAN alone. Glomerular involvement was noted in 33% of patients diagnosed with PAN, suggesting an alternative diagnosis. Sequencing of the MEFV gene confirmed the presence of two pathogenic variants in 73% of FMF patients with IgA vasculitis or PAN. The majority of patients with BD were from one case series, and presented more skin, gastrointestinal, and CNS involvement than patients with isolated BD. In conclusion, FMF, particularly when supported by two pathogenic MEFV mutations, could predispose to IgA vasculitis or a PAN-like vasculitis with more perirenal bleeding and CNS involvement.